Gamma Knife Radiosurgery: An Overview of Physics, Chemistry, Biology and Neuro-medicine - Uddin, KMN; Islam, JN (Journal of Bangladesh College of Physicians and Surgeons, 2010)
The gamma knife is a highly specialized treatment unit that provides an advanced sophisticated stereotactic approach to treatment of tumour and vascular malformations within the internal structure of the head. The gamma knife delivers a single high dose of radiation emanating from 201 cobalt- 60 unit sources. All 201 beam simultaneously intersect at the same time in a pre-defined location. The treatment planning system for gamma knife radiosurgery has been developed using nonlinear programming techniques. The system optimizes the shot sizes, location and weights for gamma knife treatments. Open stereotactic technique in the 1990’s was essential for the treatment of a number of functional conditions and cystic space occupying lesions. It has an important part to play in the investigation of tumours and can help to increase the number which are accessible to treatment. It can be employed to guide not only solid instruments but also ionizing irradiation to “masslesion – targets”. It is just this combination of stereotactic guidance and narrow beam, high energy radiation to precisely defined target, is the basis of gamma knife radiosurgery . The topic on radiological physics presents a broad field, which includes physics of radiation therapy, diagnosis and nuclear medicine. The emphasis is on the basic physical principles which form a common foundation for these areas. Consequently, the topic provides both basic radiation physics, physical aspects of treatment planning and use of radiation beams. Some knowledge of the effect of ionizing radiation on living tissues is necessary, for those who wish to understand the nature of any treatment using radiation and who also wish to inform patients about such treatment. The topic relates to the effects of radiation on visible structures, in other words, cells and tissues. The radiobiological knowledge described here has been developed in relation to standard radiotherapy. Moreover, the linear quadratic model of cell killing is also applicable for single dose irradiation. DOI: 10.3329/jbcps.v28i2.5370 J Bangladesh Coll Phys Surg 2010; 28: 100-112